Semantic Level Errors of Students’ Scientific Work From Various Indonesian Island in the City of Madiun - Pramudita Septiani; Sarwaji Surwandi; Budhi Setiawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to explain and describe the language errors of semantic level in students’ scientific work from various Indonesian islands in the city of Madiun. The study was conducted at two major universities in Madiun City. The type of research used in this research is a descriptive qualitative research through observation and field note techniques as data collection techniques. The result of the data is students’ assignment papers. Data analysis techniques used in this study issharing methods or distribution methods with advanced techniques in the form of expansion (expansion) techniques and changing forms. The conclusions of this study are: (1) Usage error of similar words, consisting of (a) 88 errors of cognate pairing, (b) 79 errors of ambiguous pairing and (c) 65 errors of contended pairing. (2) Word choice (diction) errors, which consist of (a) 87 errors because do not meet the truth requirements, (b) 89 errors because do not meet the accuracy requirements, and (c) 90 errors because do not meet the standard requirements.In addition, errors in the word choices or diction occur due to factors influenced by the language that was mastered first.